1994
DOI: 10.1089/hyb.1994.13.9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Epitope Characterization of Human Monoclonal Antibodies to Hepatitis C Virus Core Antigen

Abstract: In this study we describe the establishment of two hybridoma cell lines secreting human monoclonal antibodies to the 22-kD nucleocapsid protein (core, p22) of the hepatitis C virus (HCV). For this purpose we isolated B lymphocytes from an anti-HCV positive blood donor and infected them with Epstein-Barr (EBV). We obtained several lymphoblastoid cell clones secreting antibodies to the recombinant HCV core protein. The B-cell cultures were oligoclonally expanded and two of them were fused with the (mouse:human) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…Several studies concerning B-cell epitope analysis of HCV core antigens have been documented; however, only few studies concerning B-cell antigenic determinants in NS-3 region have been reported [Nasoff et al, 1991;Koskinas et al, 1994;Siemoneit et al, 1994;Moradpour et al, 1996]. A previous study has suggested multiple B-cell antigenic regions (NS3-e, NS3-a, NS3-a/b, NS3-b/c) identified by human B cells [Hwang et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies concerning B-cell epitope analysis of HCV core antigens have been documented; however, only few studies concerning B-cell antigenic determinants in NS-3 region have been reported [Nasoff et al, 1991;Koskinas et al, 1994;Siemoneit et al, 1994;Moradpour et al, 1996]. A previous study has suggested multiple B-cell antigenic regions (NS3-e, NS3-a, NS3-a/b, NS3-b/c) identified by human B cells [Hwang et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…The HCV genotype of this donor is unknown. B cells from this donor were transformed with Epstein-Barr virus (42). The supernatants of the resulting lymphoblastoid clones were screened by ELISA with an extract of cells infected with a recombinant vaccinia virus, RMPA95, expressing the envelope proteins E1 and E2 of an HCV genotype 1a (H) strain.…”
Section: Methodsmentioning
confidence: 99%
“…Among the different anticore mAbs obtained, mAb 19D9D6 appeared to be specific for an epitope encompassed by residues 29 -33 within the main antigenic domain (9), a property shared by the major human epitope of core (10,11). Furthermore, mAb 19D9D6 is of special interest, since it detects, with a good sensitivity, viral core Ag in sera of patients with chronic HCV infection.…”
mentioning
confidence: 99%